ANALYSIS OF COST AND TIME EFFICIENCY IN CONTAINER DISTRIBUTION BETWEEN CONTAINER TRUCK AND FREIGHT TRAIN FROM INDUSTRIAL AREA TO PORT - Imayanti, Indah; Soehodho, Sutanto; Yusuf, Nahry (Smart City, 2024)
Jakarta International Container Terminal (JICT) in Tanjung Priok Port , which serves export and import containers, can serve up to 5500 TEUs daily. However, no more than 1% of the total containers are transported by freight trains, meaning that 99% of container distribution from industrial areas is carried by trailer trucks. This condition causes a long queue at the container terminal entrance, resulting in delays in the services as well. Currently, Tanjung Priok Port is connected to rail transportation from Cikarang dry port with the frequency of twice a day with 30 flatcars (FC) for each trip. The capacity of one series of freight trains from Cikarang dry port to Tanjung Priok Port can reach 30 Feus or 60 Teus. However, the container distribution using freight trains is still less optimal because of the double handling at the JICT emplacement which is located outside JICT and the use of trailer trucks to move the containers from the area to JICT. The cost of transporting export and import containers always increases year by year because of the slow transportation due to inefficiency of the container depot location in Tanjung Priok area. In this research, the method used to determine the efficiency of container transportation is divided into three scenarios. The first scenario is when the container is fully transported by truck from the industrial area. The second scenario is when the container is transported by train and handled twice while entering JICT. Finally, the third scenario is when the JICT emplacement is located inside the JICT area, changing the business process of containers coming in and out, needing no stacking in the JICT container yard, relocating the container depot placement, consolidating containers, and automating equipment at JICT to reduce the cost and time of containers for export and import. After analyzing the costs and time of the three scenarios, it was found that the third scenario could reduce travel costs and shorten container time when exporting and importing. The 3rd scenario can reduce the cost by almost 50% from the 1st and 2nd scenarios due to container consolidation.